Microeconomic Theory second edition : Concepts and Connections. - Wetzstein, Michael E. (Taylor and Francis, 2013)
This book introduces the main concepts of microeconomics to upper division undergraduate students or first year graduate students who have undergone at least one elementary calculus course. The book fully integrates graphical and mathematical concepts and offers over 150 analytical examples demonstrating numerical solutions. The book has a strong theoretical basis but shows how microeconomics can be brought to bear on the real world. New Features for this edition include:an incorporation of the theory of stock externalities associated with greenhouse gasesdevelopm.